4b+7=6b+3-b

Simple and best practice solution for 4b+7=6b+3-b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b+7=6b+3-b equation:


Simplifying
4b + 7 = 6b + 3 + -1b

Reorder the terms:
7 + 4b = 6b + 3 + -1b

Reorder the terms:
7 + 4b = 3 + 6b + -1b

Combine like terms: 6b + -1b = 5b
7 + 4b = 3 + 5b

Solving
7 + 4b = 3 + 5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-5b' to each side of the equation.
7 + 4b + -5b = 3 + 5b + -5b

Combine like terms: 4b + -5b = -1b
7 + -1b = 3 + 5b + -5b

Combine like terms: 5b + -5b = 0
7 + -1b = 3 + 0
7 + -1b = 3

Add '-7' to each side of the equation.
7 + -7 + -1b = 3 + -7

Combine like terms: 7 + -7 = 0
0 + -1b = 3 + -7
-1b = 3 + -7

Combine like terms: 3 + -7 = -4
-1b = -4

Divide each side by '-1'.
b = 4

Simplifying
b = 4

See similar equations:

| 4.9(3.6-x)+3=2.1-7.36 | | 3(4x-3)+3=10x+2 | | d*-8.4=-10.2 | | -4(x+5)=8x-20 | | 7(x+2)+3=11-4+7x | | 9y=-18(-3-0.5y)-54 | | sqrt(2x-4)+sqrt(x+1)=1 | | 2x+-3=-4x+9 | | -3(-6b+1)=105 | | 2x-5-x=21+10x | | -6(5p+8)=-288 | | 1.2x-2.5=0.7x-0.3 | | 2(1+7b)=-96 | | 8y-29=y-15 | | -4x+7(4+4x)=-140 | | 7x^2=29x+30 | | 2x-3=-4+9 | | 4(5x-3)+16=16x-4 | | 15=x-1-3x | | 4(w-3)-7=-3(-7w+5)-9w | | 3x+8(5x-7)=-314 | | -10-14x=-9x | | 3x+16+4x=-12-x-28 | | -3(1-5r)+7=124 | | -6x+4=2x+4 | | 15*3x=105 | | x+(11.64)=-6.96 | | 3(n+5)+3=26 | | -3(6a+2)=138 | | 4(1+7v)-6=222 | | 7y-52=y+2 | | 0.66x+4=2x+4 |

Equations solver categories